POLITIK HUKUM PEMBUBARAN ORGANISASI KEMASYARAKATAN DALAM PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 2 TAHUN 2017 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 17 TAHUN 2013 DAN DIKAITKAN DENGAN KETENTUAN PASAL 22 AYAT (1) UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Anggitta, Ribka; Indra, Mexsasai; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
This study discusses about the Political Law of Dissolution of SocialOrganizations in Government Regulation in Lieu of Law No. 2 of 2017. Thehistory of the publication is based on the government's claim that Law No. 17 of2013 on Community Organizations is not effective in preventing the massorganizations that are against the Pancasila. Prior to this Lieu of Law, the case ofthe dissolution of mass organizations was carried out through the District CourtHowever, in Lieu of Law No. 2 of 2017 Chapter 80A which stipulates that inrevocation of certificates registered by the Minister at the same time declareddissolved. The President shall have the right to enact a Government Regulationin lieu of law. As this is not in accordance with the state of Indonesia when theissuance of this lieu of law. The aims of writing this thesis are; First, to knowwhat is the political law in Government Regulation Substitute Law No. 2 of 2017.Second, to know whether Lieu of Law No. 2 of 2017 in accordance with theprovisions of Chapter 22 Point (1) of the Constitution The Republic of Indonesiaof 1945.This research is normative legal type research in finding the truth ofcoherence. This normative legal research uses secondary data, the data collectingtechnique of this research is using literature studies.From the results of the research, there are two main things that can beconcluded. First, the legal politics of the establishment of Lieu of the Law No. 2 of2017 is the process of dissolution of accelerated social organizations in terms ofits mechanism; Secondly, the appropriateness of crucial meanings between Lieuof the Law. No. 2 of 2017 and the provisions of Chapter 22 Point (1) of The 1945Constitution is not fully fulfilled. The writer's suggestion, Firstly, in forming thelaw the government have to establish the direction of the policy with theobjectives of the state of Indonesia; Secondly, the President should analyze theelements of the interests of the force based on the considerations of the experts oflaw as well as the consideration of state circumstances.Keywords: Political Law - Dissolution - Mass Organization